2013
DOI: 10.1094/pdis-12-12-1201-re
|View full text |Cite
|
Sign up to set email alerts
|

tale-Based Genetic Diversity of Chinese Isolates of the Citrus Canker Pathogen Xanthomonas citri subsp. citri

Abstract: Pathotype A of Xanthomonas citri subsp. citri, the cause of citrus bacterial canker (CBC), is assumed to have originated in southern China. PthA, a type III secreted transcriptional activator-like effector (TALE), is a major pathogenicity determinant in X. citri subsp. citri. To investigate the diversity of X. citri subsp. citri in China, genomic and plasmid DNA of 105 X. citri subsp. citri isolates, collected from nine citrus-growing provinces of China, were digested by BamHI and hybridized with an internal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The bacterial strains and plasmids used in this study are listed in Table (see Supporting Information). The Xcc strains were cultivated in NB medium or NB containing 1.5% agar (NA) at 28 °C (Ye et al ., ). Escherichia coli strains were routinely cultured in Luria–Bertani (LB) medium at 37 °C.…”
Section: Methodsmentioning
confidence: 97%
“…The bacterial strains and plasmids used in this study are listed in Table (see Supporting Information). The Xcc strains were cultivated in NB medium or NB containing 1.5% agar (NA) at 28 °C (Ye et al ., ). Escherichia coli strains were routinely cultured in Luria–Bertani (LB) medium at 37 °C.…”
Section: Methodsmentioning
confidence: 97%
“…Low genetic variability was observed for strains isolated in the northern part of the country, but more diversity was present in the strains isolated in the southern part, where the disease was more prevalent (Jaciani et al, 2012). In China, several Xcc strains from nine citrus-growing regions were characterized and compared for the variability of TALEs (Ye et al, 2013). The result of the analysis of 105 strains with differential pathogenicity on a set of citrus hosts showed that the strains varied in the number of TALEs, ranging from three to five pthA genes (Ye et al, 2013).…”
Section: Xanthomonad Pathogenomementioning
confidence: 99%
“…Previous reports have shown a great variability in the size of the pthA genes from different X. citri strains (Al‐Saadi et al ., ; Gochez et al ., ; Lee et al ., ; Ye et al ., ). Given the mode of action of these TALE proteins, it is expected that this variability will contribute to explain differences in pathogenicity among the strains.…”
Section: Resultsmentioning
confidence: 97%
“…The existence of the pthA4 AT gene is perhaps just an accident, a by‐product of a recombination event in the course of effector evolution. Interestingly, Ye and colleagues () showed that two further strains of X. citri (029‐2 and 049) with attenuated virulence and reduced bacterial growth in planta were characterized by the absence of the 3.4‐kb band characteristic of the pthA4 gene, and by the appearance of a smaller band of around 2.4 kb, in a similar way to X. citri A T (Fig. ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation